PKA from Mucor circinelloides: Model to study the role of linker I in the interaction between R and C subunits - Ocampo, Josefina (2007)
Protein kinase A from the fungus Mucor circinelloides shows high affinity interaction between regulatory (R) and catalytic (C) subunits. Its R subunit shows a differential presence of several acidic residues in linker I region, in the amino terminus. Mutants R1, lacking the N-terminal region, and R2, lacking the acidic cluster, were used to analyze its effect on the interaction with the C subunit, assessed through inhibition of catalytic activity and cAMP activation of reconstituted holoenzyme. A similar decrease in the interaction was obtained when using R1 and R2 with the homologous C subunit; however when using heterologous bovine C, only R1 had a decreased interaction. The results show the general importance of linker I region in the R-C interaction in protein kinases A and point to the importance of the acidic cluster present in the N-terminus of M. circinelloides R subunit in the high affinity interaction between R and C in this holoenzyme.